Binge drinking e consumo excessivo de bebida alcoólica em jovens universitários: um enfoque junguiano - Toledo, Rafaela Boiczuk de (2014)
The present study aimed to investigate the binge drinking and excessive drinking among a group of young college students, in order to comprehend which motivations, perceptions and fantasies are involved in the compulsive alcohol drinking. The binge drinking is a harmful alcohol consumption pattern very common among the university population, able to cause various harmful consequences. Population consisted of 21 college students, 11 women and 10 men, aged between 20 and 30 years old, from several graduation courses in the city of Curitiba and who had at least one episode of binge drinking in the last year. There were conducted interviews and applied three instruments on each participants (Alcohol Use Disorders Identification Test, Social Adjustment Scale Factor / Neuroticism and projective technique of drawing with themed story). The material collected was analyzed qualitatively using Bardin s Content Analysis. Theoretically the analysis was based on the assumptions of Analytical Psychology. It was concluded that the excessive drinking and binge drinking are part of the studied sample s daily life indicating a trivialization of binge drinking among these young people, who are not able to symbolize their psychological suffering therefore they adopt a regressive and compulsive posture